The production function methodology for estimating the value of spectrum. Issue 1 (February 2015) - Prasad, Rohit
Abstract: The estimation of production functions for wireless communications markets presents particular challenges including the lumpy nature of spectrum use, and the presence of significant upfront investment. In this paper a systematic study of production functions for wireless markets is undertaken, using data from India. The efficacy of two major functional forms, the Cobb Douglas and the translog functions, are compared by benchmarking the values of spectrum they yield against the values generated by the intuitive but data-intensive cash flow method, and the prices revealed in two auctions. The comparisons allow us to conclude that factoring the lumpy nature of spectrum use by considering 'effective spectrum' data rather than raw spectrum data, and relaxing the assumption of constant elasticity of substitution are useful in obtaining accurate estimates of spectrum value. Highlights: Use of production functions to estimate the value of spectrum. Data from Indian telecommunications market. Benchmarked to cash flow method and to prices from two auctions. Assumption of constant elasticity of substitution is restrictive. Heterogeneous usage of a spectrum block needs to be factored into the analysis.